The Relationship between the Level of Satisfaction of Dental Students in the Appearance of Anterior Teeth in Terms of Orthodontic Treatment at Universitas Prima Indonesia - Rusip, Gusbakti; Suci Erawati; Daniel Yantonius Simamora (HM Publisher, 2024)
One aspect of appearance that increases self-confidence among students is having an aesthetic smile. To achieve this, it is important to pay attention to the anterior teeth because the appearance of the teeth determines aesthetic appeal. If the anterior teeth experience malocclusion, this has an impact on reducing the level of self-confidence, creating difficulty interacting socially, and creating dissatisfaction with the appearance of the anterior teeth for students. To fill the gap, this study aims to further investigate the relationship between the satisfaction level of the dental education undergraduate study program in the appearance of anterior teeth in terms of orthodontic treatment at Universitas Prima Indonesia. A total of 44 respondents were students of the dental education undergraduate study program who were sampled in the study using the online survey method. This study used univariate and bivariate analysis through SPSS v.24. There is a significant relationship between fixed orthodontic treatment and the satisfaction of the appearance of the anterior teeth of UNPRI dental education undergraduate students.